Axo-axonic cells in neuropsychiatric disorders: a systematic review - Vivien, Juliette; El Azraoui, Anass; Lheraux, Cloé; Lanore, Frederic; Aouizerate, Bruno; Herry, Cyril; Humeau, Yann; Bienvenu, Thomas C. M. (Frontiers in Cellular Neuroscience, 2023)
Imbalance between excitation and inhibition in the cerebral cortex is one of the main theories in neuropsychiatric disorder pathophysiology. Cortical inhibition is finely regulated by a variety of highly specialized GABAergic interneuron types, which are thought to organize neural network activities. Among interneurons, axo-axonic cells are unique in making synapses with the axon initial segment of pyramidal neurons. Their potential key role in physiology is mirrored in disease. Indeed, alterations of axo-axonic cells have been implicated in disorders including epilepsy, schizophrenia and autism, in which they may have critical etiological importance. Despite the recognized therapeutic potential of restoring normal axo-axonic function, evidence for axo-axonic roles in disease has only been examined in opinion reviews. By performing a systematic review of axo-axonic cells deficits in epilepsy, schizophrenia and autism spectrum disorder, we outline convergent findings and discrepancies in the literature. Overall, the implication of axo-axonic cells in neuropsychiatric disorders might have been overstated. Additional work is needed to assess initial, mostly indirect, findings and to unravel how defects in axo-axonic cells translates to cortical dysregulation and, in turn, to pathology.